Association between problematic Internet use and specific Internet activities and COVID-19- and earthquake-related stress, anxiety, and depression symptoms among Croatian young adults - Kovačić Petrović, Zrnka; Peraica, Tina; Blažev, Mirta; Kozarić-Kovačić, Dragica (Frontiers in Psychiatry, 2023)
Background: During the COVID-19 pandemic and concomitant earthquakes in Croatia in 2020, increased Internet use (IU) and Internet-based addictive behaviors were associated with decreasing mental well-being. We determined the changes IU, problematic IU (PIU), and problematic specific Internet activities in young adults during the prolonged stress caused by the pandemic and earthquakes, age differences in PIU and differences in perceived source of stress (pandemic or earhquakes), and association between PIU and increase in specific Internet activities and stress, anxiety, and depression symptoms in young adults. Methods: A cross-sectional online survey conducted from September 30, 2021 to October 17, 2021 included 353 young adults aged 22.6±2.1 years, 382 early adults aged 32.1±4.4 years, and 371 middle-aged adults aged 49.0±6.5 years. Data on sociodemographic characteristics, stressors (without perveived stressors, only pandemic-related stressor, only earthquake-related stressor, and both pandemic- and earthquake-related stressors), and U were collected with a self-report questionnaire. The Impact of Event Scale and the Hospital Anxiety Depression Scale were used to evaluate mental symptoms. PIU was assessed using Tao et al’s criteria. Data were anaylzed with paired-sample Wilcoxon test, McNemar’s and Pearson’s chi‒square tests, and structural equation modelling. Results: In 17% of young adults, we found increased PIU (OR=5.15, 95% CI [2.82, 10.18]), problematic social media use (OR=2.77, 95% CI [1.56, 5.14]), and uncontrolled online shopping (OR=5.75, 95% CI [1.97, 22.87]) (p<0.001 for all). PIU and problematic social media use were more common among young adults (60.8%), as well as problematic online gaming (25.9%). Problematic social media use was more frequent among young adults reporting pandemic stress than among those without perceived stress (69.9% vs. 43.2%). Increased online gaming predicted more severe avoidance symptoms (p=0.041), increased social media use predicted more severe depression symptoms (p=0.017), increased online shopping predicted more severe intrusion (p=0.013) and anxiety symptoms (p=0.001). PIU predicted more severe intrusion (p=0.008), avoidance (p=0.01), anxiety (p<0.001), and depression (p=0.012) symptoms. Conclusion: Different effects of the pandemic and earthquakes on Internet use could reflect a different effect of various stressors on Internet behavior of young adults. Type of problematic Internet behavior may predict for the type of mental health problem.